Difficulties associated with the diagnosis of bipolar affective disorderin a 16-year-old boy treated in the past for ADHD and ODD – case study - Chojnowska-Ćwiąkała, Izabela; Świerczyńska, Justyna; Weryszko, Małgorzata; Szpringer, Monika (Current Problems of Psychiatry, 2025)
Aim. The aim of this article is to discuss the difficulties and complexities of the bipolar affective disorder (BPAD) diagnostic process in an adolescent. The case of suspected occurrence of bipolar affective disorder in an adolescent who was diagnosed with attention deficit hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD) in childhood was presented.Case report. A 16-year-old boy was treated in the past for ADHD and ODD. The reason for the current admission to the pediatric psychiatry ward was the behavioral change that disturbed the caregivers: he has become more restless, irritable, explosive. A few nights prior to hospitalization, he was very agitated, chaotic, physically and verbally aggressive. At admission he was disorganized, tense, in strong hand manipulation anxiety. He displayed alternating attention and loquacity. His statements were chaotic, his thinking accelerated. He displayed grandiose delusions. He was uncritical. After the treatment, mood, psychomotor drive and circadian rhythms stabilisation were achieved. Discharged from the ward with the recommendation of further outpatient treatment and continuation of psychotherapeutic interactions.Conclusions.• The diagnosis of bipolar affective disorder in adolescents is a complex and difficult process. The expression of symptoms of this disorder during adolescence is different than in adults.• Differential diagnosis of bipolar affective disorder for a 16-year-old boy should also consider b oth past ADHD and ODD and their possible sequelae should be taken into account, as well as the risk of abnormal personality development.• Due to the high dynamics of changes associated with the adolescence period, further pharmacological treatment of bipolar affective disorder should be combined with psychotherapeutic interventions.